Psychophysical estimation of acid intensity and determination of sweet-acid interaction in a fish paste containing glycerol - Sánchez Pascua, Gabriela Leonor (2010)
In a fish paste made with cooked Brazilian flathead (Percophis brasiliensis), glycerol (17%), sodium chloride (1.5%) and potassium sorbate (0.1%) the following acid percentages: 0.2; 0.4; 0.6; 0.8, 1 and 1.5% w/w were incorporated to determine the relationship between added acetic acid and the sensorially perceived intensity, and the effects of the combination of sweet-acid tastes. Tests for paired comparison, ranking and structured verbal scales for sweet and acid attributes and psychophysical test were carried out. There was a perceptible difference among samples for differences of 0.4 units of acid concentration. Samples indicated as sweeter by 89.47% of the judges were those containing a lesser acid concentration. A reduction in glycerol sweetness when increasing acid levels was observed. Acetic acid reduced the sweetness of glycerol and inversely glycerol reduced the acidity of acetic acid. The data obtained with the magnitude estimation test agree with Steven’s law.